FACTORS AFFECTING PERFORMANCE ACADEMIC STUDENTS IN WEST SUMATRA - Inge Angelia; Naufal Raid; Donna Ikranova F (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Learning motivation, peer association and lecturer competence are factors that can affect student academic achievement. Based on an initial survey of 10 students in West Sumatra, it was found that 6 people had low academic achievement. This study aims to determine the factors that influence student academic achievement in West Sumatra Province in 2023. The research was conducted quantitatively using an analytic observational survey approach with a Cross Sectional design. The research aims to find out the relationship between learning motivation, peer association, lecturer competence and academic achievement in West Sumatra Province in 2023. This research was conducted in West Sumatra Province with students in tertiary institutions with 154 respondents. Data were analyzed with univariate and bivariate using the Chi-Square test. The results showed that more than half of the respondents had low academic achievement (32.5%), low learning motivation (50.6%), negative peer association (56.5%), incompetent lecturer competence (49.4%). Based on statistical tests, there is a significant relationship between learning motivation (p=0.000), peer association (p=0.001), lecturer competence (p=0.003) and academic achievement. The results of the study can be concluded that there is a relationship between learning motivation, peer association, lecturer competency and academic achievement. Based on the results of this study, it is hoped that tertiary institutions can improve lecturer competency, increase student learning motivation and student peer association in order to increase student academic achievement.